Byzantine culture in translation - Brown, Amelia Robertson; Neil, Bronwen, 1969- (Byzantina Australiensia,, 2017)
This collection on Byzantine culture in translation, edited by Amelia Brown and Bronwen Neil, examines the practices and theories of translation inside the Byzantine empire and beyond its horizons to the east, north and west. The time span is from Late Antiquity to the present day. Translations studied include hagiography, history, philosophy, poetry, architecture and science, between Greek, Latin, Arabic and other languages. These chapters build upon presentations given at the 18th Biennial Conference of the Australian Association for Byzantine Studies, convened by the editors at the University of Queensland in Brisbane, Australia on 28-30 November 2014. Contributors include: Eva Anagnostou-Laoutides, Amelia Brown, Penelope Buckley, John Burke, Michael Champion, John Duffy, Yvette Hunt, Maria Mavroudi, Ann Moffatt, Bronwen Neil, Roger Scott, Michael Edward Stewart, Rene Van Meeuwen, Alfred Vincent, and Nigel Westbrook.